PENGARUH COOPERATIVE LEARNING MODEL TIPE TEAM GAMES TOURNAMENT (TGT) TERHADAP KEMAMPUAN RENANG GAYA BEBAS PADA SISWA KELAS X SMA PGRI CIKAMPEK - Afrizal, Fauzan Noer; Gani, Ruslan Abdul; Kurniawan, Febi (Jurnal Porkes, 2025)
This research seeks to examine the impact of the team games tournament (TGT) cooperative learning strategy on enhancing freestyle swimming abilities among grade ten students at SMA PGRI Cikampek. A quasi-experimental approach was utilized, applying a nonequivalent control group designTwo groups of students participated in the study: the experimental group, which received instruction through the TGT cooperative learning model, and the control group, which was taught using traditional methods. Data collection involved administering both a pretest and posttest, utilizing a swimming skills assessment tool that had previously undergone and passed a feasibility evaluation. The results of the descriptive analysis indicated that the experimental group experienced a notable improvement in posttest scores compared to the control group. Since the normality test showed that the data on score differences did not follow a normal distribution, the Mann-Whitney U test was employed to examine the research hypothesis. The results indicated a significance value of 0.005 (p < 0.05), suggesting a statistically significant difference between the two groups. These findings demonstrate that the TGT model is effective in enhancing students’ freestyle swimming abilities by promoting collaboration and creating an engaging learning environment.